Bifidobacterium animalis subsp. lactis BL-99 ameliorates colitis-related lung injury in mice by modulating short-chain fatty acid production and inflammatory monocytes/macrophages. Issue 2 (3rd January 2023) - Nan, Xinmei; Zhao, Wen; Liu, Wei-Hsien; Li, Yalan; Li, Na; Hong, Yanfei; Cui, Jiaqi; Shang, Xuekai; Feng, Haotian; Hung, Wei-Lian; Peng, Guiying
Abstract : Oral administration of BL-99 can enrich the beneficial SCFA-producing bacteria, restrain the pathogenic microbes and preclude the infiltration of pulmonary inflammatory monocyte/macrophage, therefore alleviating colitis-related lung injury. Abstract : Pulmonary inflammation as one of the extraintestinal manifestations of ulcerative colitis (UC) has attracted extensive attention, and its pathogenesis is closely related to gut dysbiosis. Bifidobacterium animalis subsp. lactis BL-99 (BL-99) can alleviate osteoporosis caused by UC, but less research has been done on other extraintestinal manifestations (EIM) caused by UC. This study aimed to explore the role and potential mechanisms of BL-99 on DSS-induced pulmonary complications in colitis mice. The results showed that BL-99 decreased weight loss, disease activity index score, colonic pathology score, and the production of pro-inflammatory cytokines ( e.g., TNF-α, IL-1β, and IL-6) in colitis mice. BL-99 also alleviated DSS-induced lung pathological damage by suppressing the infiltration of pro-inflammatory cytokines, inflammatory monocytes, and macrophages. Furthermore, 16S rRNA gene sequencing showed lower abundances of several potentially pathogenic bacteria ( e.g., Burkholderia, Shigella, and Clostridium perfringens ) and enrichment in specific beneficial bacteria ( e.g., Adlercreutzia and Bifidobacterium animalis ) in colitis mice with BL-99 treatment. Targeted metabolomics suggested that BL-99 intervention promoted the production of intestinal acetate and butyrate. Finally, we observed that the pulmonary expression of primary acetate and butyrate receptors, including FFAR2, FFAR3, and, GPR109a, was up-regulated in BL-99-treated mice, which negatively correlated with inflammatory monocytes and macrophages. Altogether, these results suggest that BL-99 might be utilized as a probiotic intervention to prevent the incidence of colitis-related lung injury owing to its ability to shape the intestinal microbiota and suppress inflammation.